La cartographie du déplacement : les fleuves et les autoroutes dans le film « River of Fundament » de Matthew Barney et Jonathan Bepler - Silvia Néri (Études Caribéennes)
River of Fundament is Matthew Barney's last movie cosigned by the composer Jonathan Bepler, produced by Matthew Barney and Laurenz Foundation. Inspired of the novel Ancient Evening by Norman Mailer, the movie is movie-opera where the images and the musical score establish themselves together in an eclectic and laminated description. The central scene of the movie is the wake for the writer Norman Mailer (disappeared in 2007) who is presented as a dinner on a boat, "Boat of Ra", funeral boat transporting the apartment of Mailer. The boat is the main character of the travel in the American rivers on fund of urban American landscapes in Los Angeles, Detroit and New York. In this intervention, I am going to analyze the mapping of the travel in the landscape, which follows the rivers and the highways: starting from Los Angeles to River Rouge and from Detroit River, the heart of the region of the car industry, to East Rivet of New York, the rivers and the highways are the indications of the geographical travel of the history of the movie. The topographic route of images presented in the movie is a very effective way to bring the spectator through the United States.